2020
DOI: 10.1001/jamanetworkopen.2020.23942
|View full text |Cite
|
Sign up to set email alerts
|

Association of Addition of Ablative Therapy Following Transarterial Chemoembolization With Survival Rates in Patients With Hepatocellular Carcinoma

Abstract: IMPORTANCE Hepatocellular carcinoma (HCC) is a heterogeneous disease with many available treatment modalities. Transarterial chemoembolization (TACE) is a valuable treatment modality for HCC lesions. This article seeks to evaluate the utility of additional ablative therapy in the management of patients with HCC who received an initial TACE procedure. OBJECTIVE To compare the overall survival (OS) and freedom from local progression (FFLP) outcomes after TACE alone with TACE that is followed by an ablative treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…4, 5), it can also be found that radiofrequency ablation (RFA) applied to early HCC has also been studied in HCC [32]. Furthermore, RFA and TACE are also the hot spots of many researchers [33‒35].…”
Section: Discussionmentioning
confidence: 99%
“…4, 5), it can also be found that radiofrequency ablation (RFA) applied to early HCC has also been studied in HCC [32]. Furthermore, RFA and TACE are also the hot spots of many researchers [33‒35].…”
Section: Discussionmentioning
confidence: 99%
“…For patients who had previously received surveillance after initial TACE, our ML model was consistent in recommending combination local modalities for PFS benefit. Our institution 10 along with other groups 25,29 has previously demonstrated the potential advantage of additional ablative treatment modalities after TACE, which included patients with advanced tumors and tumor with complete response on imaging after initial TACE. In addition, the model recommended an alternative combination treatment in approximately one third of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we analyzed an expanded subset of a previously reported 10 institutional cohort of HCC treated with TACE with and without consolidative SBRT or RFA. The overall aim is to assess the feasibility for a ML model to predict survival in the definitive management of patients previously treated with TACE, with the goal of identifying patients who may benefit from a specific modality of LDT using SBRT or RFA.…”
Section: Introductionmentioning
confidence: 99%
“… 7 These dual synergies (combination therapy) of TACE and MWA have led to overall improved primary efficacy and progression-free survival in larger tumor cases when compared with monotherapy TACE. 8 However, this treatment strategy requires two interventional procedures to be delivered upfront instead of one.…”
mentioning
confidence: 99%